Microbial network fragmentation at a coal washing hotspot: Assembly mechanisms and stability implications - Senhua Jiang; Yangkun Shi; Jing Zhang; Chenyu Huang; Yue Li; Wenbo Zhang; Jinghui Ma; Nan Chen; Longfei Shu; Cheng Wang; Feifei Liu; Bo Wu (Applied Soil Ecology, 2026)

Autophagy in Aquatic Animals: A Double‐Edged Sword in Environmental Stress Response and Nutritional Mitigation Strategies - Hui Gao; Yue Liu; Xiuling Li; Wenxia Wang (Reviews in Aquaculture, 2026)
The intensification of aquaculture and global climate change expose aquatic animals to multifaceted environmental stressors, triggering diverse stress‐response cascades to mitigate cellular damage and preserve physiological homeostasis. Autophagy, an evolutionarily conserved lysosome‐dependent catabolic process that degrades damaged or redundant cellular components to maintain cellular homeostasis and physiological functions, plays a crucial role in the environmental stress response in aquatic animals. This review systematically summarizes the modulatory influence of major environmental stressors (physical, chemical, and biological) on autophagic activity in aquatic species. Overall, the regulatory network mainly centers on oxidative stress responses, mitochondrial quality control, the 5′‐adenosine monophosphate‐activated protein kinase (AMPK)/mechanistic target of rapamycin kinase complex 1 (mTORC1) signaling axis, mitogen‐activated protein kinase (MAPK) cascade, endoplasmic reticulum (ER) stress and related pathways. The dynamic equilibrium of autophagic flux dictates the cellular fate balance between adaptive survival and stress‐induced injury: physiologically moderate autophagy functions as a cytoprotective and adaptive mechanism that confers stress resilience, whereas dysregulated autophagy (either impaired flux or excessive activation) disrupts cellular homeostasis and shifts cell fate toward apoptotic death. Additionally, this review explores the potential of nutritional intervention strategies to modulate autophagic activity and alleviate stress‐induced damage in aquatic animals. Finally, key challenges and prospective research directions are proposed, providing a theoretical framework for deciphering stress resistance mechanisms in aquatic animals and advancing sustainable aquaculture practices.

Adaptability of Chaetomorpha valida (Ulvophyceae) spores to salinity, nutrients and water flow in aquaculture ponds and its invasive evaluation - Dongyue Li; Ronglian Xing; Rui Li; Xuebin Cao; Shujun Hu; Xiaojing Pan; Hongxia Zhang; Lihong Chen; Zhen Yu (Aquatic Ecology, 2026)

Acupoint hot compress for labor-pain management: a randomized, parallel-group, controlled trial - Fangfang Wang; Leyi Fu; Xinyue Li; Yuqun Pu; Lianqing Gong; Lin Zhou; Lanxiang Fu; Yaping Chen; Mali Chen; Yue Qin; Xiaoying Lyu; Ye Zhang; et al. (Journal of Zhejiang University-SCIENCE B, 2026)

Variations of soil multifunctionality across different soils and its divergent responses to the exposure of copper and sulfadiazine - Aiju Liu; Fangshuo Zhang; Yunna Wang; Zafran Gul Wazir; Mingyue Li; Hongliang Liu (Applied Soil Ecology, 2026)

Molecular and biological characterisation of Magnaporthe oryzae botourmiavirus 15 - Yuxin Wu; Weilan Wu; Cong Li; Xinyi Li; Hui shuang Yi; Yue lin Li; Pan Gong; Songbai Zhang; Shouguo Fang; Qingchao Deng (Archives of Virology, 2026)

Intercropping enhances aggregate stability on acidic red-soil slopes via an arbuscular mycorrhizal fungi-mediated glomalin-enzyme pathway - Ruolan Tang; Qirui Wang; Huahui Li; Xiongxing Pu; Wanting Li; Benshuai Yan; Ting Wang; Zilin Wang; Maopan Fang; Xinyue Li; Yongmei Li; Jixia Zhao (Applied Soil Ecology, 2026)

Rhizosphere metabolite changes induced by coniferous-broadleaved tree mixing shift soil bacterial community structure in coniferous forests - Yue Liu; Chunjing Jiao; Wanju Feng; Bing Yang; Yuchun Yang; Lixue Yang; Fang Wang (Applied Soil Ecology, 2026)

Long-term straw substitution for chemical fertilizers promotes an increase in phosphorus availability in greenhouse soils by modulating the microbial community structure - Diwen Yang; Ling Ma; Leixin Yu; Tianqi Wang; He Gao; Yue Liu; Lijuan Yang (Applied Soil Ecology, 2026)

Litter-mediated shifts in microbial communities along an altitudinal gradient enhance humification-driven soil organic carbon accumulation - Xiaojun Qi; Yiting Wang; Mengyao Zheng; Zhiyue Liu; Yanbo Ren; Yuan Li; Tong Jia (Applied Soil Ecology, 2025)

Soil clay content determined the temperature response of N2O emissions derived from denitrification - Lixin Jia; Hanhan Yang; Yong Li; Zhangliu Du; Xiaotang Ju; Yue Li; Di Wu (Applied Soil Ecology, 2025)

Soil microbial community harboring key genes drives rhizosphere phosphorus mobilization of phosphorus-accumulating Polygonum hydropiper - Daihua Ye; Yuyue Lin; Tao Liu; Xizhou Zhang; Yu Tang; Keji Wang; Huagang Huang; Haiying Yu; Yongdong Wang; Xinhua He; Tingxuan Li (Applied Soil Ecology, 2025)

mTOR Signaling in Aquaculture Animals: A Central Nutrient‐Sensing Hub Orchestrating Growth, Metabolism, Health and Quality - Yue Liu; Kangsen Mai; Wenbing Zhang (Reviews in Aquaculture, 2025)
Functioning as a master coordinator, the mechanistic target of rapamycin (mTOR) coordinates nutrient availability and energy status to fundamental biological processes including growth, metabolism, and physiological homeostasis through evolutionarily conserved mechanisms. The capacity of mTOR to assimilate nutritional and metabolic signals places it as a central focus in aquaculture nutrition research. This review systematically synthesizes current knowledge on the regulatory mechanisms mediated by the mTOR in various physiological processes of aquatic animal species, with particular emphasis on the mTOR networks regulated by diverse dietary nutrients. It provides a comprehensive summary of the regulation of various feed ingredients in growth performance, metabolic homeostasis, immune responses, product quality optimization, and health maintenance via mTOR. Moreover, this review analyzes interspecies variations and dietary adaptations across aquatic animals and outlines future research prospects focusing on the mTOR networks. It aims to establish a scientific framework for advancing precision nutrition research by integrating molecular regulatory insights with dietary nutrients, ultimately facilitating efficient and sustainable aquaculture.

Long-term manure and straw addition enhance protistan diversity and stimulate soil microbial interactions and nutrient mineralization in vegetable field - Yinjie Zhang; Wei Gao; Shaowen Huang; Chenyang Li; Jiwei Tang; Qian Zhang; Mingyue Li; Yilun Wang; Chao Ai (Applied Soil Ecology, 2025)

Potential effect of biogas slurry application to mitigate of peak N2O emission without compromising crop yield in North China Plain cropping systems - Zhichao Zou; Yue Li; Xueqin Ren; Zichao Zhao; Zhangliu Du; Di Wu (Applied Soil Ecology, 2025)

12-year N addition enhances soil organic carbon decomposition by mediating microbial community composition in temperate plantations - Xinyi Wu; Yanyan Liu; Hongjin Zhang; Lizheng Dong; Yiping Zuo; Xiaoyue Li; Wei Wang (Applied Soil Ecology, 2025)

Soil biological nitrogen fixation is closely associated with soil ammonium nitrogen content in a mowing semiarid natural grassland - Jiaojiao Liu; Jiayue Liu; Shuwen Wang; Qiang Fu; Taogetao Baoyin; Zhihua Bao; Frank Yonghong Li (Applied Soil Ecology, 2024)

The influence of soil depth and tree age on soil enzyme activities and stoichiometry in apple orchards - Chuanyu Gao; Chunyue Li; Le Zhang; Huan Guo; Qianxue Li; Zhaoyang Kou; Yifan Li (Applied Soil Ecology, 2024)

An explainable integrated machine learning model for mapping soil erosion by wind and water in a catchment with three desiccated lakes - Hamid Gholami; Mehdi Jalali; Marzieh Rezaei; Aliakbar Mohamadifar; Yougui Song; Yue Li; Yanping Wang; Baicheng Niu; Ebrahim Omidvar; Dimitris G. Kaskaoutis (Aeolian Research, 2024)

Effects of bed sediment conditions on debris flow propagation from the two-phase flow modelling perspective - Binghan Lyu; Yue Li; Peng Hu (Advances in Water Resources, 2024)

Dynamics of global dryland vegetation were more sensitive to soil moisture: Evidence from multiple vegetation indices - Huanhuan Liu; Yue Liu; Yu Chen; Mengen Fan; Yin Chen; Chengcheng Gang; Yongfa You; Zhuonan Wang (Agricultural and Forest Meteorology, 2023)